الثقافة التنظيمية و علاقتها بالانتماء التنظيمي - مساعيد, أم السعد; دمدوم, ندى الوجدان (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة نظراً لأهمية دور الثقافة التنظيمية للمؤسسات الحكومية في تحديد اتجاهات الموظفين فيها و انتمائهم اختار الباحث تناول بعدي الثقافة التنظيمية و الانتماء التنظيمي بالدراسة للوقوف على طبيعة العلاقة بينهما , كما هدفت هذه الدراسة للتعرف على تصورات الموظفين نحو الثقافة التنظيمية وعلى مستوى الانتماء التنظيمي لدى موظفي محافظة الغابات بولاية الوادي , و عليه فإن هذه الدراسة تسعى للإجابة على التساؤل الرئيسي : ما طبيعة العلاقة بين الثقافة التنظيمية و الانتماء التنظيمي في محافظة الغابات بولاية الوادي ؟ و للإجابة على تساؤلات الدراسة قام الباحث بصياغة الفرضية العامة التالية : توجد علاقة بين الثقافة التنظيمية و الانتماء التنظيمي في محافظة الغابات بولاية الوادي كما تندرج تحت هذه الفرضية الفرضيات الجزئية التالية : • توجد علاقة بين الثقافة التنظيمية في بعدها الإداري و الانتماء التنظيمي في محافظة الغابات بولاية الوادي • توجد علاقة بين الثقافةالتنظيميةفيبعدها الإنسانيوالانتماء التنظيمي فيمحافظة الغاباتبولايةالوادي • يختلف مستوي الانتماء التنظيمي في محافظة الغابات بولاية الوادي باختلاف الخصائص الشخصية للموظفين ( الجنس و العمر و المستوى التعليمي و المستوى الرتبي و الخبرة المهنية ) كما إعتمدت هذه الدراسة على المنهج الوصفي و استخدم طريقة المسح الشامل حيث تكون مجتمع الدراسة من جميع الموظفين و اعتمد الباحث على أداة الاستبيان كوسيلة أساسية لجمع المعلومات . أظهرت نتائج الدراسة ما يلي : • أن هناك علاقة طردية وموجبة قوية بين الثقافة التنظيمية و الانتماء التنظيميحيث أنه كلما زادت قوة الثقافة التنظيمية بمؤسسة محافظة الغابات بولاية الوادي زاد ذلك من مستوى الانتماء التنظيميللموظفين بها . • وجود علاقة بين البعد الاداري للثقافة التنظيمية و الانتماء التنظيمي . • وجود علاقة بين البعد الانساني للثقافة التنظيمية و الانتماء التنظيمي . • أظهرت النتائج أنه لا يوجد اختلاف في مستوى الانتماء بين البيانات الشخصية الثلاثة ( الجنس , المؤهل العلمي , المستوى الرتبي ) كما أظهرت النتائج أنه يوجد اختلاف في مستوى الانتماء بين متغيري ( العمر , الخبرة المهنية ) . Abstract Given the importance of the role of organizational culture in government institutions in determining the attitudes of employees and their affiliation, the researcher chose to study the two dimensions of organizational culture and organizational affiliation to determine the nature of the relationship between them. This study also aimed to identify employees' perceptions of organizational culture and the level of organizational affiliation among the employees of the forest governorate in El-Oued state. Accordingly, this study seeks to answer the main question: What is the nature of the relationship between organizational culture and organizational affiliation in Forest province in El-Oued state? In order to answer the questions of the study, the researcher formulated the following general hypothesis: There is a relationship between organizational culture and organizational affiliation in Forest province in El-Oued state. The following partial hypotheses also fall under this hypothesis: • There is a relationship between the organizational culture in its administrative dimension and the organizational affiliation in Forest province in El-Oued state • There is a relationship between organizational culture in its human dimension and organizational affiliation in Forest province in El-Ouedstate • The level of organizational affiliation in Forest province in El-Oued state differed according to the personal characteristics of the employees (sex, age, educational level, rank level, and professional experience). This study also relied on the descriptive approach and used the comprehensive survey method, where the study population consisted of all employees, and the researcher relied on the questionnaire tool as a basic method for collecting information The results of the study showed the following: • That there is a strong direct and positive relationship between organizational culture and organizational affiliation, as the stronger the organizational culture in the Forestry Governorate Corporation in El-OuedState, the greater the level of organizational affiliation of its employees. • The existence of a relationship between the administrative dimension of organizational culture and organizational affiliation • The existence of a relationship between the human dimension of organizational culture and organizational affiliation • The results showed that there is no difference in the level of belonging between the three personal data (sex, educational qualification, rank level) and the results also showed that there is a difference in the level of belonging between the variables (age and professional experience).
دراسة ميدانية في مؤسسة محافظة الغابات بولاية الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الثقافة التنظيمية، culture organisationnelle, organizational culture; الإنتماء التنظيمي، affiliation organisationnelle, Organizational affiliation